The harbor - Engberg, Katrine, 1975- (Scout Press, 2022)
"Copenhagen-based police detectives Jeppe Korner and Anette Werner are on a new case--their deadliest yet--in the newest thriller from the internationally bestselling author of The Tenant and The Butterfly House"--